2009
DOI: 10.1159/000261808
|View full text |Cite
|
Sign up to set email alerts
|

Setting Overweight Adults in Motion: The Role of Health Beliefs

Abstract: Objective: Health beliefs of overweight adults who did and did not enter an exercise program were compared to identify possible factors that hamper people to enter such a program. Method: Participants (n = 116, 78 women and 38 men) were overweight adults without comorbidities. Self-report instruments examined the burden of suffering, beliefs related to physical exercise and obesity, somatic complaints, and obesity-related quality of life of new participants of exercise programs versus sedentary non-exercisers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…This model explicates that if pain is (mis)interpreted as being threatening, avoidance of physical activity results and this subsequently has a negative impact on musculoskeletal function, physical performance, and fitness [ 39 ]. The present study confirms the suggestion that comparable to chronic pain patients and the findings in sedentary but otherwise healthy overweight adults [ 40 ], fear of injury can be a barrier to engage in physical activity and a contributor to the sedentary state of patients after bariatric surgery. When someone avoids physical activity due to fear, the fear cannot extinguish.…”
Section: Discussionsupporting
confidence: 90%
“…This model explicates that if pain is (mis)interpreted as being threatening, avoidance of physical activity results and this subsequently has a negative impact on musculoskeletal function, physical performance, and fitness [ 39 ]. The present study confirms the suggestion that comparable to chronic pain patients and the findings in sedentary but otherwise healthy overweight adults [ 40 ], fear of injury can be a barrier to engage in physical activity and a contributor to the sedentary state of patients after bariatric surgery. When someone avoids physical activity due to fear, the fear cannot extinguish.…”
Section: Discussionsupporting
confidence: 90%
“…Another recent addition to the HBM is the concept of perceived control which is a measure of level of self-efficacy, or one's confidence in the ability to successfully perform an action. Although devised to examine behaviour change within a health setting (see for example, alcohol use [Minugh et al, 1998;Von et al, 2004], smoking [Von et al, 2004], drug use [Bonar & Rosenberg, 2011;Welch, 2000], exercise [James et al, 2012;Wouters et al, 2009] and medical screening behaviours [Austin et al, 2002;Yarbrough & Braden, 2008]),the model is flexible enough to usefully explore different domains and table 1 demonstrates how the HBM can be considered within a financial security context.…”
Section: Using the Health Belief Model As A Way Of Understanding Usermentioning
confidence: 99%
“…22,38 Thus, more knowledge on body image (profiles) may elucidate when body image acts as a barrier or may be a cue to action for weight changing behaviour. 39 Therefore, this observational cross-sectional study assessed body image, measured by appearance evaluation, appearance orientation and body size perception discrepancy, in a large sample of the Dutch population including all weight groups (i.e., underweight, normal weight, and class I, II and III obesity). This study focused specifically on women due to the body image differences compared to men.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research showed that people who are invested in appearance and at the same time consider themselves unattractive are more likely to pursue weight changing or cosmetic surgery 22,38 . Thus, more knowledge on body image (profiles) may elucidate when body image acts as a barrier or may be a cue to action for weight changing behaviour 39 …”
Section: Introductionmentioning
confidence: 99%